2017
DOI: 10.1093/neuonc/nox081
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of tumor-associated macrophages in glioma neo-angiogenesis and implications for anti-angiogenic strategies

Abstract: "Tumor-associated macrophages" (TAMs) form a significant cell population in malignant tumors and contribute to tumor growth, metastasis, and neovascularization. Gliomas are characterized by extensive neo-angiogenesis, and knowledge of the role of TAMs in neovascularization is important for future anti-angiogenic therapies. The phenotypes and functions of TAMs are heterogeneous and more complex than a classification into M1 and M2 inflammation response types would suggest. In this review, we provide an update o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 115 publications
4
117
0
Order By: Relevance
“…Malignant potential of glioma cells depends critically on their capacity to transgress through the basement membrane [135,136], migrate through the extracellular matrix [137], reach and enter proximally located microvasculature, travel to distant sites [138], exit the microvasculature, and implant and grow in distant microenvironments [139]. Neoangiogenesis induced by protein factors released from glioma cells contributes to sustaining tumoral growth [140]. Evasion of immune responses by downregulation of cell surface expression of tumor specific antigens and negative immunomodulators contributes to immune evasion by glioma cells [125].…”
Section: Drug Developmentmentioning
confidence: 99%
“…Malignant potential of glioma cells depends critically on their capacity to transgress through the basement membrane [135,136], migrate through the extracellular matrix [137], reach and enter proximally located microvasculature, travel to distant sites [138], exit the microvasculature, and implant and grow in distant microenvironments [139]. Neoangiogenesis induced by protein factors released from glioma cells contributes to sustaining tumoral growth [140]. Evasion of immune responses by downregulation of cell surface expression of tumor specific antigens and negative immunomodulators contributes to immune evasion by glioma cells [125].…”
Section: Drug Developmentmentioning
confidence: 99%
“…A few studies have demonstrated that the amount of TAMs in a tumor are closely linked to the number of blood vessels in human cancers [43-46]. Tumor growth is characterized by hypoxia, therefore macrophages are recruited to hypoxic areas of the tumor.…”
Section: The Role Of Tams On Tumor Angiogenesis Crc Growthmentioning
confidence: 99%
“…We wanted to investigate whether AVNP2 had a similar effect on gliomas. This time, we found that AVNP2 could not only modulate the tumour associated inflammation but also the levels of inflammation-related proteins such as IL-1β, IL-6, TNF-α and NF-ĸB, which all together play an indispensable role in the formation, growth, infiltration and metastasis of gliomas (Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 90%